[Letter from Andrew Young, Mayor of Atlanta, to Congressman Andrew Jacobs Jr regarding defecit reduction and fairness] (Tufts Archival Research Center, 2007)
Letter from Andrew Young, Mayor of Atlanta, to Congressman Andrew Jacobs Jr regarding defecit reduction and fairness. Accuses excise taxes of unfairly burdening the lower and middle class. Opposes taxing general goods rather than luxury goods. Urges Jacobs to oppose proposals for increases in excise taxes.